TAKDIR KEHIDUPAN MANUSIA DALAM PERSPEKTIF HADITS - Syifa Roudhatul Jannah; Muhammad Alif (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2026)
Destiny (qadar) is one of the pillars of faith that holds a crucial place in Islamic teachings and has a significant influence on human perspectives on life. The concept of destiny is not only related to theological beliefs but also shapes human mental attitudes and behavior in facing various events, such as success, failure, disaster, and death. However, in practice, this understanding of destiny often suffers from errors, both in the form of an attitude of resignation without effort and a tendency to deny the role of Allah SWT's will in human life. This study aims to examine the concept of destiny in human life based on the hadiths of the Prophet Muhammad (peace be upon him). The research was conducted using library research and a thematic hadith approach (maudhu'i). This involved collecting and reviewing hadith related to the theme of destiny. These hadith were then analyzed and grouped into several main themes, such as the belief in destiny, the determination of destiny in human life, and the relationship between destiny and human endeavor.The study's findings indicate that the hadiths of the Prophet Muhammad (peace be upon him) provide a balanced understanding of the concept of destiny. Destiny is understood as the definite and comprehensive decree of Allah SWT, yet it does not negate the role of human effort, prayer, and responsibility. Thus, the concept of destiny in Islam directs humans to have strong faith in Allah SWT's will while remaining active in their endeavors in life.